Surgical Guides (Patient-Specific Instruments) for Pediatric Tibial Bone Sarcoma Resection and Allograft Reconstruction. (24th February 2013) - Bellanova, Laura; Paul, Laurent; Docquier, Pierre-Louis
Abstract : To achieve local control of malignant pediatric bone tumors and to provide satisfactory oncological results, adequate resection margins are mandatory. The local recurrence rate is directly related to inappropriate excision margins. The present study describes a method for decreasing the resection margin width and ensuring that the margins are adequate. This method was developed in the tibia, which is a common site for the most frequent primary bone sarcomas in children. Magnetic resonance imaging (MRI) and computerized tomography (CT) were used for preoperative planning to define the cutting planes for the tumors: each tumor was segmented on MRI, and the volume of the tumor was coregistered with CT. After preoperative planning, a surgical guide (patient-specific instrument) that was fitted to a unique position on the tibia was manufactured by rapid prototyping. A second instrument was manufactured to adjust the bone allograft to fit the resection gap accurately. Pathologic evaluation of the resected specimens showed tumor-free resection margins in all four cases. The technologies described in this paper may improve the surgical accuracy and patient safety in surgical oncology. In addition, these techniques may decrease operating time and allow for reconstruction with a well-matched allograft to obtain stable osteosynthesis.